2021
DOI: 10.3389/fpls.2021.622062
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning-Based Vision System Combining Detection and Tracking for Fast On-Line Citrus Sorting

Abstract: Defective citrus fruits are manually sorted at the moment, which is a time-consuming and cost-expensive process with unsatisfactory accuracy. In this paper, we introduce a deep learning-based vision system implemented on a citrus processing line for fast on-line sorting. For the citrus fruits rotating randomly on the conveyor, a convolutional neural network-based detector was developed to detect and temporarily classify the defective ones, and a SORT algorithm-based tracker was adopted to record the classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Convolution Neural Network (CNN) achieves superior performance in computer vision tasks such as classification ( Chen et al, 2021 ), object detection ( Kang and Chen, 2020a ), and segmentation ( Kang and Chen, 2020b ). Here, we applied a 50-layer CNN model Residual-Network (ResNet-50) to directly predict the storage time of the oranges based on the images obtained, which was also treated as a classification task.…”
Section: Methodsmentioning
confidence: 99%
“…Convolution Neural Network (CNN) achieves superior performance in computer vision tasks such as classification ( Chen et al, 2021 ), object detection ( Kang and Chen, 2020a ), and segmentation ( Kang and Chen, 2020b ). Here, we applied a 50-layer CNN model Residual-Network (ResNet-50) to directly predict the storage time of the oranges based on the images obtained, which was also treated as a classification task.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers used a modified ResNet-50 model to extract the features of tomato surface defects and classify images of tomato defects ( Da Costa et al, 2020 ). Chen et al (2021) established an online citrus sorting system, shown in Figure 17 , and a detector named Mobile-citrus based on Mobile-V2 to identify surface defects in citrus. Then, the arms of robots arms pick out the defective ones with the linear Kalman filter model used in predicting the future path of the fruits.…”
Section: Convolutional Neural Network-based Fresh Fruit Detectionmentioning
confidence: 99%
“…Several types of the 3D visual sensors exist on the market, such as stereo cameras, Light Detection and Ranging sensors (LiDAR) and RGB-D (RGB-depth) cameras (Jayakumari et al 2021;Chen et al 2021). The practical applications of these cameras are shown in Fig 3, with the maximum number of applications focused on the stereo cameras.…”
Section: Sensorsmentioning
confidence: 99%